Antiproliferative Activity of Cissus quadrangularis L. Extract Against Human Cervical Cancer Cells: In Vitro and In Silico Analysis - Siddiqui, Sahabjada; Zia, Qamar; Abbas, Mohd; Verma, Sushma; Jafri, Asif; Misra, Deepika; Luqman, Suaib; Ahamed, Maqusood; Ahmad, Mohd S.; Arshad, Mohd (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Cervical cancer is the second leading cause of cancer in women, which necessitates safe and potential therapeutic agents. Objective: This study was designed to investigate the antiproliferative effect of ethanolic extract of Cissus quadrangularis L. (CQ) against human cervical adenocarcinoma HeLa cell line and in silico analysis of selected active agents against apoptosis executioner enzyme caspase-3. Methods: Cell viability was analyzed in HeLa cells at different concentrations (25-300 μg/ml) of CQ extract. Reactive oxygen species (ROS) generation, cellular apoptosis, cell cycle analysis and caspases-3 activation were evaluated. In silico, structure-based virtual screening analysis was carried out using AutoDock Vina and iGEMDOCK. Results: Cell viability of HeLa cells was reduced significantly (p < 0.05) in a dose-dependent manner, however, CQ extract showed non-toxic to normal kidney epithelial NRK-52E cells. CQ extract induced the intracellular ROS level, nuclear condensation and reduced the mitochondrial membrane potential (MMP) with the induction of annexin V-FITC positive cells. CQ extract arrested cells in G0/G1 and G2/M checkpoints and activated caspase-3 activity significantly in HeLa cells. The molecular docking study showed a strong binding affinity of CQ phytocomponents against the caspase-3 (PDB ID: 1GFW) protein of human apoptosis. PASS analyses of selected active components using Lipinski’s Rule of five showed promising results. Further, drug-likeness and toxicity assessment using OSIRIS Data Warrior V5.2.1 software exhibited the feasibility of phytocomponents as drug candidates with no predicted toxicity. Conclusion: This study suggested that active constituents in CQ extract can be considered as potential chemotherapeutic candidates in the management of cervical cancer.
Keywords: Caspase-3